THE IMPACT OF THE IMPLEMENTATION OF THE HUMAN RESOURCE INFORMATION SYSTEM (HRIS) ON EMPLOYEE PERFORMANCE - Nadia Ulfa; Rafikha Anggraini; Deni Apriadi; Haikal Rifanda (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Rapid technological advances have led to significant changes in organizational work patterns and systems. Based on these conditions, this study aims to examine the impact of the implementation of the Human Resource Information System (HRIS) on labor performance. This research applies a qualitative approach through literature study methods and literature review as the main data source. The discussion focused on the analysis and comparison of various theories and relevant research findings in order to expand the understanding of the concepts and frameworks used. The results of the literature review show that the implementation of HRIS has a strategic role in the management of human resource administrative activities, including attendance management, payroll systems, benefits, and employee incentives. The use of HRIS allows the entire process to run in an integrated and real-time basis, thus making a real contribution to improving the efficiency and effectiveness of the Human Resources Department (HRD) performance in managing employee data and information.